PENGEMBANGAN KOTA BOGOR SEBAGAI DESTINASI PARIWISATA INTERNASIONAL - Mulyana, Bedi (Jurnal Ilmiah Pariwisata, 2012)
The research aims to identify factors that became a tourist attraction in the city ofBogor, Indonesia (supply side) and discussed the international tourists who visited this city(demand side). In addition to the enhancements described with the support of the localgovernment that serves as a facilitator for the development of tourism in terms of the BogorCity’s policies and planning. A regional area of the city’s tourist development is veryimportant to promote development and improve the interconnected regional economy,including the development of the city as international tourist destination. The study wasconducted by survey techniques (questionnaire surveys, interviews and observation andstudy of literature to support the research) using the approach of demand and supply in theBogor City tourism development as an international tourist destination. The study'sfindings can be considered for Bogor City tourism development as an internationaldestination. Furthermore, the government together with other tourism stakeholders mustcoordinate and cooperate in realizing the Bogor City tourism development that better inthe future.